“Bilik Deteksi Dini Stunting”: Inovasi Deteksi Dini Dan Edukasi Pencegahan Stunting Pada Balita Kelurahan Krembangan Utara Kota Surabaya - Arhab Nashrullah; Adhisty Mutiara Isnain; Belarmino Gaudencio De C.; Karina Dewi Anggraeni; Siti Khotimah; Shofiyatun Hasanah; Muhammad Rafly Bouty; Anita Rizki Rahmawati Asror; Zahrotun Nur Faidah; Airatul Kibtiyah; Afifah Irfa'ul Ilmiyyah; Aslin Nuroniyah Azzahra; Dwica Sri Lestari; Ahmad Athoillah; Citra Rynda Oktavia; Nazma Sheny Latifa; Asysya Ashla; Paramita Viantry (CV. SINAR HOWUHOWU, 2026)
Stunting remains a serious chronic nutrition problem in Indonesia, with a national prevalence of 19.8 percent in 2024, including in urban areas such as RW 02, Pesapen Village, Krembangan Utara, Surabaya. Most parents of children under five in this area were unfamiliar with early stunting screening and had never received education on regular monitoring of children's nutritional status. The